MEDICATION READER FOR THE VISUALLY IMPAIRED - Aguiar, Jefferson Jorge Maruca Baptista de; Arthur; JUNIOR, Edemar Ferrarezi; Antonio, Fabricio Domingues (Revista Interface Tecnológica, 2024)
The Lemevi project aims to create an assistive device for visually impaired individuals, facilitating the identification of medications through tag reading. Developed to enhance user autonomy and safety, the device faces challenges such as reading accuracy and durability. Arduino was chosen for its versatility and low cost, enabling rapid and effective prototyping. The research combined qualitative and quantitative methods, including interviews with visually impaired individuals and device testing. These methods helped tailor Lemevi to user needs, resulting in a robust and reliable product. Design adjustments and continuous improvements were based on feedback from testing, confirming the device’s effectiveness in tag reading. The addition of a mobile data chip update system represents a significant advancement, expanding the device’s functionality to other areas such as food and beverages. The project demonstrates a commitment to social inclusion and quality of life improvement, with prospects for partnerships to make the device accessible to low-income individuals. It is an innovative solution that highlights the importance of Arduino in developing assistive technologies.